2019
DOI: 10.1177/0002716219856544
|View full text |Cite
|
Sign up to set email alerts
|

Who Goes Next? The Gendered Expansion of Mexican and Senegalese Migrant Sibling Networks in Space and Time

Abstract: The migration literature shows that individuals whose siblings have migrated abroad are more likely to migrate, yet we know little about sibling migrant networks. We use MMP and MAFE-Senegal survey data to compare migration patterns in two very disparate contexts (Mexico and Senegal) in an attempt to assess the scope, manner, and generalizability of sibling network migration patterns. Our results show that while Senegalese families are likely to have one international migrant, Mexican families are likely to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Hoang (2011) observed that men use larger acquaintanceship networks to inform and support migration, whereas women build on family networks (cf. Riosmena & Liu, 2019), also for social protection. A further insight from relational approaches is that the “network effects” that are confirmed by social network analysis are in part a result of individual agency.…”
Section: Three Phases Of Migrationmentioning
confidence: 99%
“…Hoang (2011) observed that men use larger acquaintanceship networks to inform and support migration, whereas women build on family networks (cf. Riosmena & Liu, 2019), also for social protection. A further insight from relational approaches is that the “network effects” that are confirmed by social network analysis are in part a result of individual agency.…”
Section: Three Phases Of Migrationmentioning
confidence: 99%
“…In addition, gender is a highly relevant, although often ignored, element in this research field. Evidence indicates that migrant men tend to use broader networks of acquaintances for example when looking for support, while migrant women rely more heavily on immediate and extended family (Hoang 2011;Riosmena and Liu 2019;Lin 2000). Also, being married and having children contribute positively to more frequent interactions with new and existing social contacts (e.g.…”
Section: 2mentioning
confidence: 99%
“…Social networks related to blood connections are vital in terms of facilitating migration among youth. Sibling ties that brothers and sisters have on each other stand out as being useful in facilitating the subsequent migrations of their siblings (Massey & Espinosa 1997;Massey & Aysa-Lastra 2011;Liu 2013in Riosmena & Liu 2019. Individuals may be more likely to draw on social capital emanating from sibling ties since high expectations are common on brothers and sisters to help one another in times of need.…”
Section: Rural Social Network and Youth Migrationmentioning
confidence: 99%
“…Individuals may be more likely to draw on social capital emanating from sibling ties since high expectations are common on brothers and sisters to help one another in times of need. As such, the norm continues to exist in most, if not all, societies, especially in low-and middleincome nations (Cicirelli, 1994in Riosmena & Liu, 2019. Indeed, new migrants often choose destinations based on the presence of ties and, especially, in the expectation that some social ties will be more valuable than others in assisting during a moment of need (Sue et al, 2019).…”
Section: Rural Social Network and Youth Migrationmentioning
confidence: 99%